TEACHING SPEAKING USING SHOW AND TELL GAME: A QUALITATIVE STUDY OF SIXTH GRADE STUDENTS - Julia Rizky Dinihari; Lusiana Suciati Dewi; Slamet Wahyudi Yulianto (Bajang Institute, 2026)
This study looks at how well the Show and Tell game works for boosting sixth graders’ speaking skills. Researchers focused on 22 students at SDN Purwawinaya during the 2025/2026 school year. They gathered information by watching classroom activities, interviewing students, and collecting related documents. At first, many students struggled with speaking English. They didn’t feel confident, didn’t know enough words, had a hard time pronouncing things correctly, and often hesitated to speak. But once teachers started using the Show and Tell game in three meetings, there were clear changes. The kids spoke up more, joined in with activities, and could put sentences together more smoothly. Bringing in visual aids and letting students use objects from home helped them express their thoughts better and made standing up in front of the class less scary. All in all, using games like Show and Tell made the classroom a friendlier, more relaxed place where students felt okay about making mistakes. The results show the Show and Tell game really works for building fluency, growing students’ vocabulary, and raising their confidence when they speak.